BASIC FACTORS OF ISLAMIC EDUCATION MANAGEMENT PHILOSOPHY: SYSTEMATIC LITERATURE REVIEW APPROACH - M. Alang Khairun Nizar Bin Ismail; Usiono (CV. RADJA PUBLIKA, 2024)
The implementation of Islamic educational institutions as an organizational system must apply quality-based management to be able to compete amidst increasingly complex pressures from other educational institutions and the current digital era 4.0. This article aims to explain the basic factors of Islamic education management philosophy.The method used in this article is qualitative research approachSystematic Literature Review. Article articles are collected from Google Scholar via PRISMA flow (Preferred Reporting Item for Systematic Reviews and Meta-analyses). Then descriptive content analysis was carried out.The results found thatThe basic factor of philosophy in Islamic education management is an education system that prioritizes a humane managerial system. Education Management: In implementing Islamic education, more effort is required. A systems approach or systemic thinking is one of the fundamental solutions that must be understood and implemented by every manager of an Islamic educational institution aimed at uncovering the factors that influence the Islamic education system model. Education Personnel: The success of improving the quality of education is closely related to the professionalism of teaching staff and educational staff. This strategic position cannot be replaced by any sophisticated technology, because the existence of sophisticated technology still requires educators to operate it.